IDENTIFIKASI FASAD BANGUNAN ACTIVITY SUPPORT PADA KORIDOR JALAN DI KAWASAN WISATA TEGENUNGAN WATERFALL, DESA KEMENUH, GIANYAR, BALI - Made Suryanatha Prabawa; Made Yaya Sawitri; I Ketut Darma (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
The road corridors in the Tegenungan Waterfall Tourism Area are composed of various kinds of buildings, all of which accommodate the same function of trade or trade functions. The trade function is present to meet the needs of visiting tourists. These needs are food, drinks, souvenirs, transportation, etc. related to tourism. However, over time the development of the tourist area makes the growth of buildings along the road corridor in the Tegenungan Waterfall Tourism Area increasingly uncontrollable. The purpose of this study is to identify the facade components of the existing activity support buildings along the corridor of the road leading to the waterfall. The research method used is a qualitative-descriptive method, with the implementation phase of the method being a field survey accompanied by observations of buildings along the corridor road to Tegenungan Waterfall and supported by literature studies. The results of the study provide the final conclusion that the appearance of the facade of the majority of buildings uses a facade formed or arranged as a result of commodities traded based on tourist needs.